Clinical, Microbiological and Inflammatory Evidence of the Efficacy of Combination Therapy Including Serratiopeptidase in the Treatment of Periimplantitis - C. Passariello (European Journal of Inflammation, 2012)
The present study was aimed to evaluate the effect of introducing administration of the proteolytic enzyme serratiopeptidase in the combined mechanical-antibiotic treatment of periimplantitis (PI). Two randomized groups of 64 adults with a diagnosis of PI were studied over a 6-month period. All patients were treated with a combined mechanical and antibiotic protocol for 15 days. The experimental group (EG) was administered antibiotic and serratiopeptidase, while the control group was administered antibiotic alone. To evaluate the effects of the two treatment protocols, clinical and radiographic indices, the concentration of IL-lβ, IL-6 and TNF-α in the gingival crevicular fluid, the amount of total bacteria] DNA and the presence of specific bacteria were assessed at baseline and at 6 months from treatment. Success rates of combined treatments at 6 months were 96.9% and 78.1% for the EG and CG respectively ( P ≤0.01). Implants of the EG showed greater enhancement of clinical, microbiological and inflammatory parameters as compared to those of the CG. Microbiological analyses showed that resistance to combined therapy was constantly associated with the isolation of bacterial species that are not common periodontal pathogens (mainly S.aureus and P.aeruginosa) . The data demonstrate that the addition of serratiopeptidase to combined mechanical-antibiotic treatment protocols of periimplantitis significantly improves outcomes and suggest that serratiopeptidase acts at different levels during the healing process.